Introduction to a Symposium on Global Finance and the Agrifood Sector: Risk and Regulation - Jennifer Clapp; Oane Visser; Ryan Isakson (Journal of Agrarian Change, 2015)
This symposium introduction brings together two debates; the debate on global food prices and speculation, and the debate on so-called global ‘land investment’ or ‘land grabbing’. Both debates are examining two sides of the same phenomenon – the growing role of private financial investors in the global agri-food value chains and the myriad consequences of it. The symposium moves beyond the identification of finance as an exogenous factor to the trends in the sector. It examines real-life incarnations of finance in the sector by looking at investment arrangements, including connections with the state, and its (regional) variations. The symposium addresses three main themes. First, it explores the interplay of the state and private finance. It shows that the effect of regulation is limited in the face of increasingly mobile and complex investment flows. Second, it addresses the shifts and transfigurations of risk in the agri-food sector due to financialization. Third, the symposium discusses to what extent, and how, the origins and identity of farmland investors still matters within an increasingly globalized financial sector. The paper concludes by identifying some related areas for further research.